Share

# Prove Cos^(-1) 4/5 + Cos^(-1) 12/13 = Cos^(-1) 33/65 - CBSE (Science) Class 12 - Mathematics

ConceptProperties of Inverse Trigonometric Functions

#### Question

Prove cos^(-1)  4/5 + cos^(-1)  12/13 = cos^(-1)  33/65

#### Solution

Let cos^(-1)  4/5 = x. Then, cos x = 4/5 => sin x = sqrt (1 - (4/5)^2) = 3/5

:. tan x =  3/4 => x =  tan^(-1)  3/4

:. cos^(-1)  4/5 -  tan^(-1)  3/4   ...(1)

Now let cos^(-1) 12/13 = y Then cos y= 12/13 => sin y = 5/13

:. tan y = 5/12 => y = tan^(-1)  5/12

:. cos^(-1)  12/13 = tan^(-1)  5/12  --- 2

Let cos^(-1)  33/65 = z. Then cos z = 33/65 => sin z = 56/65

:. tan z = 56/33 => z = tan^(-1)  56/33

:. cos^(-1)  33/65 = tan^(-1)  56/33  ....(3)

Now, we will prove that:

L.H.S = cos^(-1)  4/5 + cos^(-1)  12/13

= tan^(-1)  3/4 + tan^(-1)  5/12   [Using 1 and 2]

= tan^(-1)  (3/4 + 5/12)/(1 - 3/4 . 5/12)      "    "       [tan^(-1) x + tan^(-1) y = tan^(-1)  (x + y)/(1-xy)]

= tan^(-1)  (36+20)/(48-15)

= tan^(-1)  56/33

= tan^(-1)  56/33    [by(3)]

= R.H.S

Is there an error in this question or solution?

#### APPEARS IN

NCERT Solution for Mathematics Textbook for Class 12 (2018 to Current)
Chapter 2: Inverse Trigonometric Functions
Q: 5 | Page no. 51
Solution Prove Cos^(-1) 4/5 + Cos^(-1) 12/13 = Cos^(-1) 33/65 Concept: Properties of Inverse Trigonometric Functions.
S